2013
DOI: 10.2503/jjshs1.82.1
|View full text |Cite
|
Sign up to set email alerts
|

Quality Maintenance of Postharvest Horticultural Crops by Stress Treatments and Approach for the Elucidation of Its Mechanism

Abstract: This review deals with the effectiveness and mechanism of stress treatments, such as heat and UV treatments (hot air, hot water, and UV-B), on the quality maintenance of postharvest green horticultural crops such as broccoli florets and green sour citrus fruits (lime, Nagato-yuzukichi, and yuzu), in which chlorophyll (Chl) degradation is a main factor in quality deterioration. Postharvest stress treatments effectively suppressed Chl degradation with senescence during storage. In broccoli florets and lime fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…(Costa, Civello, Chaves, & Martínez, 2002;Kunieda, Amano, & Shioi, 2005;Suzuki & Shioi, 2002). In the Chl catabolic pathway, pheide a is degraded to Chl catabolites by pheide a oxygenase (PaO) and red Chl catabolite reductase (Park et al, 2007;Yamauchi, 2013). The substrate of PPH is phein, and both phein a and b are catalyzed to produce phytol-free pigments and pheide a and b, respectively (Schelbert et al, 2009).…”
Section: Stress-induced Loss Of Cellular Compartmentalization Of Phenmentioning
confidence: 99%
“…(Costa, Civello, Chaves, & Martínez, 2002;Kunieda, Amano, & Shioi, 2005;Suzuki & Shioi, 2002). In the Chl catabolic pathway, pheide a is degraded to Chl catabolites by pheide a oxygenase (PaO) and red Chl catabolite reductase (Park et al, 2007;Yamauchi, 2013). The substrate of PPH is phein, and both phein a and b are catalyzed to produce phytol-free pigments and pheide a and b, respectively (Schelbert et al, 2009).…”
Section: Stress-induced Loss Of Cellular Compartmentalization Of Phenmentioning
confidence: 99%
“…UV‐C is effective in increasing the antioxidant capacity of strawberries in the post‐harvest period, in controlling the yellowing of broccoli florets, and reducing the incidence of chilling injury in stored peaches and peppers . Treatments with low and ambient UV‐B radiation (less harmful for the user than UV‐C) inhibit the yellowing of stored green fruits and vegetables and increase the antioxidant content of the produce . Recently, it has been shown that post‐harvest UV‐B treatments can improve, at least in selected genotypes, both the health‐promoting potential and the aesthetic properties of tomato and peach fruits by increasing anthocyanin contents .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Treatments with low and ambient UV-B radiation (less harmful for the user than UV-C) inhibit the yellowing of stored green fruits and vegetables and increase the antioxidant content of the produce. 6,7 Recently, it has been shown that post-harvest UV-B treatments can improve, at least in selected genotypes, both the health-promoting potential and the aesthetic properties of tomato and peach fruits by increasing anthocyanin contents. 8,9 UV wavelengths may also affect other ripening-related parameters, such as firmness, which, in strawberries, is affected by changes in the UV wavelengths transmitted by polythene films in protected cultivation.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that POD controls the availability of hydrogen peroxide in the cell wall, which is a requirement for the cross-linking of phenolic groups in response to various external stresses [ 48 ]. In addition, treatment with UV-A or UV-B increased the levels of antioxidants such as ascorbate, α-tocophol and polyphenol [ 49 ].…”
Section: Discussionmentioning
confidence: 99%